2019
DOI: 10.4081/pr.2019.7848
|View full text |Cite
|
Sign up to set email alerts
|

Sclerosing Angiomatoid Nodular Transformation Presend Nodulartransformation Presenting with Abdominal Hemorrhage: First Report in Infancy

Abstract: A limited number of sclerosing Angiomatoid Nodular Transformation (SANT) have been reported in pediatric age. We describe the first case of SANT occurring in a nine-week-old female infant that was admitted to our unit for severe abdominal distension and rectal bleeding. Enlarged spleen was detected on physical examination. Laboratory investigations revealed severe anemia and coagulation abnormalities. Abdominal ultrasound and computed tomography revealed ascites and splenomegaly with a large mass at the lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…However, occurrence of SANT shows a young age trends in recent report [6,7]. Youngest SANT patient was a 7-month-old infant with splenomegaly [8]. Most cases are found incidentally since most patients are asymptomatic.…”
Section: Discussionmentioning
confidence: 96%
“…However, occurrence of SANT shows a young age trends in recent report [6,7]. Youngest SANT patient was a 7-month-old infant with splenomegaly [8]. Most cases are found incidentally since most patients are asymptomatic.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, SANT may be indirectly associated with other cases of malignity that have comorbidities (16%, n = 37) (colorectal cancer 2.1%, gastric cancer 2.1% and lung cancer 1.3%) as SANT was detected incidentally during the follow-up of primary malignities [ [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ]. The literature reports three cases of thrombocytopenia in patients with SANT [ 6 , 73 , 77 ]. Dieobold et al [ 6 ] reported a patient presenting with thrombocytopenia due to paramyxovirus 19.…”
Section: Discussionmentioning
confidence: 99%
“…Gooch et al [ 73 ] noted that the surgical oncology consultation agreed that a splenic mass was the most likely cause of thrombocytopenia in their patient. Finally, Pelizzo et al [ 77 ] reported a case of SANT occurring in a nine-week-old female infant who was admitted with severe abdominal distension and rectal bleeding, severe anemia (Hb 4.6 g/dL), thrombocytopenia (54 × 103/μL) and coagulation abnormalities resulting from persistent abdominal hemorrhaging from ruptures of the spleen capsule that were un-responsive to blood transfusions. In the present study, no infection such as Epstein-Barr virus (EBV) infection or IGg4 was detected, and we presumed SANT to be the cause of the thrombocytopenia as the patient had normal range platelet levels after laparoscopic splenectomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations